ANALISIS KINERJA PENDAPATAN DAN BELANJA PEMERINTAH KOTA KUPANG - Revi Halim; Alfred T. Rantelobo (JAKA - Jurnal Jurusan Akuntasi, 2019)
This study aims to determine the financial performance of the City of Kupang in 2015-2018. This research is a quantitative descriptive. This research was conducted at the Regional Finance Agency of Kupang City. Data collection is done by using the documentation method. The data analysis technique used is quantitative descriptive with the formula: Decentralized Degree Ratio, Regional Financial Independence Ratio, PAD Effectiveness Ratio, Revenue Growth Ratio, Spending Efficiency Ratio, Spending Variance Ratio, Spending Growth Ratio. The analysis of the results of this study shows that the Regional Financial Performance of the City of Kupang can be seen from (1) Decentralization Degree Ratio can be categorized as less, because the average degree of decentralization is 15.79%, (2) Regional Financial Independence Ratio can be categorized as instructive because the average is 21.36% and it is known that the Central Government is more independent than the Regional Government, (3) PAD Effectiveness Ratio can be categorized as very effective, because the average effectiveness is 109.21%, (4) Revenue Growth Ratio has increased positively with average the average is 4.74%, (5) the Shopping Efficiency Ratio can be categorized as efficient because the realization of the budget is less than the target budget with an average of 88.9%, (6) The Shopping Variance Ratio is categorized as a favorite variance (preferred difference) with an average the average is 44, 8%, (7) Growth Expenditures Ratio experiences positive growth with an average of 6.17%.